Healing Process Of Burns Using Ambarella Leaf (Spondias dulcis F.) and Vaselin in Rats (Rattus norvegicus) - Ummu Balqis; Dian Masyitha; Fera Febrina (Universitas Syiah Kuala, 2014)
The aims of this research was to find out the healing process of second degree burn in rats (Rattus norvegicus) using ambarella leaf (Spondias dulcis F.) and vaselin on histopathologically. The research consisted of 4 treatment groups and 3 rats each, P1(double distilled water), P2 (ambarella leaf + double distilled water), P3 (vaselin), and P4 (ambarella leaf + vaselin). Treatment was done twice a day for 21 days. The research parameters are inflammatory reactions and distribution of collagen tissue. Data were analyzed descriptively. The results showed that on day 7, P1 and P3 many infiltration of inflammatory cells, hemorrhage and edema, on P2 and P4 here more infiltration of inflammatory cells, hemorrhage and edema. On the day 14th of many inflammatory cell infiltration, collagen tissue diffuse very thin on were described P1 and P3, and visible presence of new blood vessels was found on P4. On day 21th infiltration of inflammatory cells still present on (P1), there were a lot of new blood vessels on P2, there has been a process of epithelialization (P3), epidermis formed and collagen tissue spread very densely on P4. Based on the results of this study it can be concluded that administration of ambarella leaf and vaselin can speed up the healing process of burns in rats compared with other treatments.Key words: ambarella leaf, burn, vaselin